MERAB MAMARDASHVILI`S PHENOMENOLOGICAL MOTIVES IN THE "CARTESIAN MEDITATIONS" - Kebuladze, Vakhtang (Sententiae, 2008)
Merab Mamardashvili in his lectures on Descartes, read in 1981, attempts fenomenologizating philosophy of Descartes, finding in the Cartesian method proto-elements of the Husserl's phenomenological reduction. Husserl`s identification of the Cartesian cogito and the phenomenological concept of transcendental subjectivity is, apparently, artificial as the Cartesian elements are present in the phenomenology only in a modified form. Mamardashvili phenomenologiзирует Descartes until the denial of substantiality of thinking in his teaching and borrowing elements of Heidegger's interpretation of the identity of thinking and being in the act of cogito. For the Mamardashvili Descartes made it possible to rethink the implicit approval of the phenomenological approach in terms of ideological captivity. References